The development of a prototype computerized school library catalog for the Saint Joseph Institute of Technology, Butuan City - Cabebe, Iris A.; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
This study intended to search the background and current status of Saint Joseph Institute of Technology Library. The researcher's objective was to design a cheaper and user-friendly program for the automation of library systems using Visual FoxPro version 8 for school libraries (specifically SJIT) to utilize.
Two among the 14 educational institutions in Butuan city, namely Butuan Doctors College and Father Saturnino Urios University, have online library services bought from the Follett company. With this expensive software available in the market today paired with the poor financial status of schools in Butuan City, automation of library systems would be the last priority.
By incorporating the data gathered from SJIT library with the FoxPro database program, the researcher achieved design of a cheaper and user-friendly school library catalog for the benefit of the SJIT library and other school libraries in Butuan City. this program will be networked in the Main Library A of SJIT and used as a LANPAC (Local Area Network of Public Access Catalog) aside from the simplified cataloging system.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Saint Joseph Institute of Technonlogy Library; ALS (Computer system).; Libraries -- Automation -- Philippines -- Butuan City